Hyperphosphatemia: a novel risk factor for mortality in chronic kidney disease - Cozzolino, Mario; Ciceri, Paola; Galassi, Andrea (Annals of Translational Medicine; Vol 7, No 3 (February 01, 2019): Annals of Translational Medicine, 2018)
Cardiovascular (CV) mortality in chronic kidney disease (CKD) associate with traditional risk factors (1) including dyslipidaemia, diabetes, smoking and left ventricular mass hypertrophy. Furthermore, increasing evidence supports the role of non-traditional risk factors that associate with CV morbidity, especially vascular calcification (2). These risk factors are inflammation and altered mineral metabolism.